SORLA mediates endocytic uptake of proIAPP and protects against islet amyloid deposition - Alexis Z.L. Shih; Yi-Chun Chen; Thilo Speckmann; Esben Søndergaard; Annette Schürmann; C. Bruce Verchere; Thomas E. Willnow (Elsevier, 2022)
Objective: Sorting-related receptor with type A repeats (SORLA) is a neuronal sorting receptor that prevents accumulation of amyloid-beta peptides, the main constituent of senile plaques in Alzheimer disease. Recent transcriptomic studies show that SORLA transcripts are also found in beta cells of pancreatic islets, yet the role of SORLA in islets is unknown. Based on its protective role in reducing the amyloid burden in the brain, we hypothesized that SORLA has a similar function in the pancreas via regulation of amyloid formation from islet amyloid polypeptide (IAPP). Methods: We generated human IAPP transgenic mice lacking SORLA (hIAPP:SORLA KO) to assess the consequences of receptor deficiency for islet histopathology and function in vivo. Using both primary islet cells and cell lines, we further investigated the molecular mechanisms whereby SORLA controls the cellular metabolism and accumulation of IAPP. Results: Loss of SORLA activity in hIAPP:SORLA KO resulted in a significant increase in islet amyloid deposits and associated islet cell death compared to hIAPP:SORLA WT animals. Aggravated islet amyloid deposition was observed in mice fed a normal chow diet, not requiring high-fat diet feeding typically needed to induce islet amyloidosis in mouse models. In vitro studies showed that SORLA binds to and mediates the endocytic uptake of proIAPP, but not mature IAPP, delivering the propeptide to an endolysosomal fate. Conclusions: SORLA functions as a proIAPP-specific clearance receptor, protecting against islet amyloid deposition and associated cell death caused by IAPP.